CSR in Chavez's Venezuela - Ramos, Mariel (2008)
Governments have an important role in the development of corporate social responsibility (CSR) in their countries, and their actions combined with the needs of each society and the initiative of the private sector is what makes CSR so different across the world. This paper contributes to the debate surrounding CSR by drawing on a country specific case, that of Venezuela. The aim is to uncover the impact Hugo Chavez has in shaping CSR through the type of discourse he delivers and the legal enactments his administration drafts as well as ways they encourage CSR initiatives. The study analyses the national business system of Venezuela. The focus is on political influences wielded on society and corporations that shape this system. A variety of typologies are presented with the purpose of guiding the discussion.